WHOLE OF GOVERNMENT DALAM PENYELENGGARAAN MAL PELAYANAN PUBLIK DI KOTA PEKANBARU - Hasim As’ari; Nur Laila Meilani; Khairani Ritonga (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The Public Service Mall in Pekanbaru City has consistently received awards as the best public service provider in 2017, 2018, and 2019 so that it becomes a role model for other areas. This thesis aims to analyze how the implementation of the Public Service Mall in Pekanbaru is based on a whole of government approach using a qualitative descriptive method. Data collection techniques in this study were based on the results of interviews, observations, and documentation in the form of secondary data related to this research. The results of this study indicate that the Pekanbaru City Public Service Mall is well organized based on the consideration of the basic values ​​of the whole of government, namely the coordination that exists between the leadership and the superiors of each agency, as well as from the superiors of their respective subordinates. Then for public services incorporated in the Public Service Mall in Pekanbaru City, it is well integrated so that data and information related to the community can be more synchronized and the Public Service Mall in Pekanbaru City can reach the stage of simplifying public services both in terms of time, procedures, flow, as well as costs.